2004
DOI: 10.1021/jp0378440
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Ion−Molecule Reactions of Metal−Carbide Cations MCn+ (M=Y and La; n=2, 4, and 6) with Benzene and Cyclohexane Investigated by FTICR Mass Spectrometry and DFT Calculations

Abstract: Yttrium- and lanthanum-carbide cluster cations YC(n)(+) and LaC(n)(+) (n = 2, 4, and 6) are generated by laser ablation of carbonaceous material containing Y(2)O(3) or La(2)O(3). YC(2)(+), YC(4)(+), LaC(2)(+), LaC(4)(+), and LaC(6)(+) are selected to undergo gas-phase ion-molecule reactions with benzene and cyclohexane. The FTICR mass spectrometry study shows that the reactions of YC(2)(+) and LaC(2)(+) with benzene produce three main series of cluster ions. They are in the form of M(C(6)H(4))(C(6)H(6))(n)(+),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…However, recent quantum chemical calculations for the lanthanum carbides by Roszak and Balasubramanian [9] indicated that LaC 2 has a cyclic (or 'fan') structure. Similar results have been reported for the LaC þ 2 ion [10]. This raises the question whether the gaseous actinide carbide species also have cyclic structures.…”
Section: Introductionsupporting
confidence: 85%
“…However, recent quantum chemical calculations for the lanthanum carbides by Roszak and Balasubramanian [9] indicated that LaC 2 has a cyclic (or 'fan') structure. Similar results have been reported for the LaC þ 2 ion [10]. This raises the question whether the gaseous actinide carbide species also have cyclic structures.…”
Section: Introductionsupporting
confidence: 85%
“…In our CASPT2 calculations, the electronic ground states of ThC 2 and UC 2 adopted the symmetric triangular molecular structure I (similar to those found for rare earth dicarbides, while the asymmetric triangular structures II lie very close in energy. The bent and the two linear molecular arrangements are considerably (generally by a few hundreds of kJ/mol) higher in energy.…”
Section: Resultsmentioning
confidence: 68%
“…Similar interactions were found in the gas phase in Pd and Ni complexes with alkyl chains with two carbons or longer, 9,10 as well as in solution and in the solid phase for Ni, Pd, and Pt complexes. 19,20 It is worth noting that the energy of both axial and equatorial versions of TS4-5Pd lies below the energy of the separated reactants (selected as zero in Figure 1), consistent with the fact that the ion−molecule reactions (IMRs) are observed to occur under the near-thermal conditions of the ion trap mass spectrometer. 29,30 Scheme 2 illustrates the nomenclature for structures 1−9 and is designed to assist with the identification of structures throughout the manuscript.…”
mentioning
confidence: 54%
“…Gas-phase experimental studies in combination with density functional theory (DFT) calculations offer a unique way of dissecting complex catalytic processes into individual elementary steps . Mass spectrometric experiments with bare metal cations M + have revealed dehydrogenation of cyclohexane to benzene, while Fe + , Co + , and Ni + produce small amounts of ethylene and propylene upon the collisional activation of M + /cyclohexane complexes. Nickel­(II) cationic species CpNi + (where Cp = cyclopentadienyl) react with cyclohexane by eliminating one, two, or three hydrogen molecules . More recently, Gronert and co-workers published an elegant example of a Ni(0)/fluorenyl anionic complex dehydrogenating cyclohexane in a similar fashion …”
Section: Introductionmentioning
confidence: 99%